2011
DOI: 10.1016/j.jtcvs.2010.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between neoplastic cells and cancer-associated fibroblasts through the CXCL12/CXCR4 axis: Role in non–small cell lung cancer tumor proliferation

Abstract: Interaction between carcinoma-associated fibroblasts and tumor epithelial cells through the CXCL12/CXCR4 axis plays a role in non-small cell lung cancer tumor proliferation, marking this axis as a target for immune intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 28 publications
(48 reference statements)
1
53
0
Order By: Relevance
“…In the present study, it was observed that higher CXCR4 mRNA expression occurred in lung carcinomas with lymph node metastasis or with vascular invasion, which was in concurrence with the previous consensus of the role of CXCR4 in promotion of invasion and metastasis (13,17,18). Previous studies have reported an association between high CXCL12/SDF-1 expression and high T scores as well as an increased tendency to form lymph node metastases (18,19). In the present study, CXCL12/SDF-1 mRNA expression was significantly associated with higher TNM staging, but inversely correlated with vascular invasion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, it was observed that higher CXCR4 mRNA expression occurred in lung carcinomas with lymph node metastasis or with vascular invasion, which was in concurrence with the previous consensus of the role of CXCR4 in promotion of invasion and metastasis (13,17,18). Previous studies have reported an association between high CXCL12/SDF-1 expression and high T scores as well as an increased tendency to form lymph node metastases (18,19). In the present study, CXCL12/SDF-1 mRNA expression was significantly associated with higher TNM staging, but inversely correlated with vascular invasion.…”
Section: Discussionsupporting
confidence: 92%
“…The IL-8 receptors, CXCR1 and CXCR2, have been identified in numerous tumor cells; however, the presence of these receptors has not yet been reported in lung cancer. Chemokine (C-C motif) receptor (CCR)7, which is the receptor for two major chemokines, chemokine (C-C motif) ligand (CCL) 19 and CCL21, was also demonstrated to have an important role in tumor metastasis and was associated with poor prognosis (9,10). The aim of the present study was to investigate the role of three chemokine ligand-receptor pairs, CXCL12-CXCR4, CXCL8-CXCR1/CXCR2, CCL19/CCL21-CCR7, in the malignant progression and metastasis of lung carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic studies indicated that CXCL12 mediated the proliferation of cancer cells, which may be related to activation of Akt, Erk, Akt-1/FOXO-3␣, Stat-3, and etc. (7,20,21,30,31). Although additional study is warranted to elucidate the correlation between rapamycin anti-proliferation activity and cxcl12 expression, this finding further supports that mTOR inhibitor may be useful for gastric cancer therapy.…”
Section: Discussionmentioning
confidence: 53%
“…NSCLC cells expressing CXCR4 were noticed to migrate to tissues or organs with a high level of CXCL12, such as lymph nodes, contralateral lung, liver, brain, and bone marrow (Phillips et al, 2003;Belperio et al, 2004;Su et al, 2005;Wagner et al, 2009), even if the primary tumor was resected, just as Wang et al (2014) found that a high expression level of CXCR4 correlated with brain-specific metastasis following complete resection of NSCLC. In addition, the axis can promote cell proliferation, tumor growth, and angiogenesis (Phillips et al, 2003;Wald et al, 2011), and CXCR4 also appears to have an effect on the biology of cancer stem cells, which possess high self-renewal capacities, potential recapitulation of tumors in ectopic settings, and drug-resistant properties in NSCLC (Eramo et al, 2008;Wald et al, 2011). NSCLC cells expressing CXCR4 are strong candidates for those stem cells that maintain their property of self-renewal through a CXCR4-mediated signal transducer and activator of transcription 3 (STAT3) pathway (Jung et al, 2013).…”
Section: Cxcl12/cxcr4mentioning
confidence: 99%
“…Extracellular Ub, a recently identified new ligand for CXCR4, was found to act as an anti-inflammatory immune modulator in hematopoietic cells, and to induce suppressive and apoptotic effects on these cells (Saini et al, 2010;Majetschak, 2011). Recent studies on the potential role of extracellular Ub in non-hematological cells found that it had anti-apoptotic effects via activation of the PI3K Belperio et al, 2004;Su et al, 2005;Eramo et al, 2008;Wagner et al, 2009;Damelin et al, 2011;Montuori et al, 2011;Wald et al, 2011;Almasi et al, 2013;Jung et al, 2013;Hu et al, 2014;Li and Tai, 2014;Wang et al, 2014 Nrf2: NF-E2-related factor 2; EGFR: epidermal growth factor receptor; uPAR: urokinase plasminogen activator receptor; Ub: ubiquitin; DARC: Duffy antigen receptor for chemokines; CCX-CKR: ChemocentryX chemokine receptor. References in bold: chemokines/ receptors with anti-tumor effect pathway and was related to cell migration in epithelial cells.…”
Section: Ubiquitin/cxcr4mentioning
confidence: 99%